Electron precipitation and ionospheric disturbance - Torr, Marsha R (Rhodes University, Faculty of Science, Department of Physics, 1966)
From Introduction: The minimum in the scalar magnitude of the geographic total field, which lies off the coast of Brazil, allows the mirror points of trapped particles to dip low into the atmosphere over the South Atlantic Ocean, resulting in two regions of maximum intensity of preciptated particles in that region, one from the inner belt and one from the outer. High charged particle fluxes have been observed at low altitudes over these regions by satellites Sputnik 5 and 6 (Ginsburg et al, 1961) and Discoverer 31 (Seward and Kornblum, 1963) amongst others. The more southerly of these two regions acts as a sink for electrons from the outer radiation belt and will be referred to in what follows as the Southern Radiation Anomaly. Gladhill and van Rooyen (1963) predicted that the energy deposited in the upper atmosphere by these charged particles would be sufficient to give rise to enhanced geophysical effects such as auroral emission, X-rays and ionization and heating of the upper atmosphere in this region. Although some of these effects have been correlated with precipitated electrons, no definite relation had until now been established between ionospheric effects and precipitated particles. The aim of this thesis was to investigate such a relationship and the results were extremely successful. It will be shown conclusively in what follows, that the precipitation of electrons can account for the ionospheric disturbances defined by a disturbance criterion at all stations around L=4. Part I describes the exploration of the radiation belts and the magnetosphere with rockets and satellites. The resulting theoretical models based on the observations are discussed. A brief review is given of the work that has been done to date to derive equations for the loss and replenishment of particles in the belts. Because of the complexity of these and the number of doubtful factors involved, a simple model of injection of electrons into the outer belt is devised, giving average values of trapped and precipitated electron fluxes at any point around L=4. In Part II, this model is employed together with the disturbance criterion of Gledhill and Torr (1965) to examine the relationship between ionospheric disturbances and electron fluxes. Also the energy range of the precipitated particles is examined.
Keywords: Electrons; Electron precipitation; Ionosphere; Ionospheric electron density